Immunological changes in nestlings growing under predation risk. (16th April 2020) - Roncalli, Gianluca; Soler, Manuel; Tieleman, B. Irene; Versteegh, Maaike A.; Ruiz‐Raya, Francisco; Colombo, Elisa; Sambla, Mercedes Gómez; Ibáñez‐Álamo, Juan Diego
Abstract : Predation is one of the most relevant selective forces in nature. However, the physiological mechanisms behind anti‐predator strategies have been overlooked, despite their importance to understand predator–prey interactions. In this context, the immune system could be especially revealing due to its relationship with other critical functions and its ability to enhance prey's probabilities of survival to a predator's attack. Developing organisms (e.g. nestlings) are excellent models to study this topic because they suffer a high predation pressure while undergoing the majority of their development, which maximizes potential trade‐offs between immunity and other biological functions. Using common blackbirds Turdus merula as model species, we experimentally investigated whether an elevated nest predation risk during the nestling period affects nestlings' immunity and its possible interactions with developmental conditions (i.e. body condition and growth). Experimental nestlings modified some components of their immunity, but only when considering body condition and growth rate, indicating a multifaceted immunological response to predation risk and an important mediator role of nestlings' developmental conditions. Predation risk induced a suppression of IgY but an increase in lymphocytes in nestlings with poor body condition. In addition, experimental but not control nestlings showed a negative correlation between growth and heterophils, demonstrating that nest predation risk can affect the interaction between growth and immunity. This study highlights the importance of immunity in anti‐predator response in nestlings and shows the relevance of including physiological components to the study of predation risk.